A heart full of headstones [compact disc, unabridged] - Rankin, Ian (Rankin, Ian. Inspector Rebus novel series., 2022)
Detective Inspector Siobhan Clarke is tasked with the city's most explosive case, which could expose her mentor John Rebus, who is now in the crosshairs both of crime lords and his fellow policemen.